Development of an innovative powder adhesive based on epoxy-polyester and lignin for production of particleboards - Miroslav Němec; Jan Janesch; Lukáš Sahula; Kateřina Hájková; Tomáš Pipíška; Pavel Král; Benjamín Petržela; Štěpán Hýsek (Case Studies in Construction Materials)
This study presents the development of innovative particleboards bonded with a hybrid powder adhesive composed of epoxy-polyester resin and kraft lignin, aiming to eliminate formaldehyde and volatile organic compounds (VOCs) from the manufacturing process. While powdered epoxy-polyester adhesives are well established in the metal and automotive sectors, their application in wood composites remains largely unexplored and only limited research has explored their potential for particleboard production. Particleboards were manufactured using varying proportions of kraft lignin (0–100 %) to partially or fully replace the epoxy-polyester base. The optimal performance was observed with 20 % lignin substitution, where mechanical properties such as modulus of rupture (MOR = 8.3 MPa), modulus of elasticity (MOE = 1455 MPa), and internal bond (IB = 0.21 MPa) were comparable to or exceeded those of the control variant without lignin. Despite lower mechanical performance at high lignin ratios (≥80 %), 100 % lignin-based boards exhibited improved thermal stability and fire resistance, confirmed by TGA, DSC, and cone calorimetry. SEM analysis revealed that lignin contributed to good particle coverage and homogeneous bonding. These results demonstrate the feasibility of using kraft lignin in powder form as a binder or co-binder in wood-based composites. Such particleboards offer a promising alternative for applications in interior non-load-bearing construction and eco-friendly furniture manufacturing.